Turkey's rise as an emerging power - (:unkn) unknown (Taylor and Francis Inc., 2016)
Turkey is emerging as an important actor in world politics, exerting growing influence both in its immediate region and beyond. This book aims to understand and explain this phenomenon, utilizing a variety of perspectives from international relations theory. One prominent issue is how Turkey, long embedded in the West via NATO and other European organizations, is growing more confident and is asserting more independent foreign policy positions. This is particularly marked in the Middle East, where some suggest Turkey is pursuing a "neo-Ottomanist" agenda. At times, this competes with and creates tensions with the West. However, a rising Turkey can also be a constructive phenomenon and complement the West. This book examines geopolitical, economic, and cultural dimensions of Turkey's rise, pointing to both Turkish success and the limits of Turkish power and influence. It includes consideration of Turkey's relations with NATO, the European Union, the Middle East, and BRIC countries. This book was published as a special issue of Turkish Studies. © 2015 Taylor & Francis. All rights reserved.